لادانی واتایی له شیعری ژنه شاعیرانی کورد له باشوری کوردستان سانی (١٩٨٠-٢٠٠٠( - فرج, دیلان سلام حمه; میرە, ئهحمهد محهمهد ڕەشید; عهبدوڵ, کانیاو بهکر (Sulaimani Journal for Humanities, 2021)
This research titled (meaning diversions in the poetry of Kurdish women poems in South Kurdistan between (1980 – 2000). Researchers answer these questions: what is diversion in meaning? What are the types of meaning diversions? This subject is important in Kurdish literature. We can say this subject has not been investigated in women’s’ poems. This research uses the method of (descriptiveanalysis) to analyze some women’s poems where they use meaning diversion. As well as some reason that lead to meaning diversion. This research consists of an introduction, two main chapters, conclusion, and references. In this research the poetry sources of these poets were cited: Kazhal Ahmad, Najeeba Ahmad, Kazhal Ibraheem Khidr, Rozh Halabjayy, Shireen . K., Nazand Bagikhani, Chnwr Nameeq, Mahabad Qaradaghi, and Sozan Mama.
Keywords: meaning diversion; sign; replacement diversion; and poetry